Perlindungan Hukum Guru Bagian dari Cerminan Tegaknya Supremasi Hukum di Sektor Pendidikan - Okti, Diana Rezu; F, Firman; N, Nurfarhanah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The case involving Supriyani, an honorary teacher in South Konawe, Southeast Sulawesi, has drawn public attention and highlighted the issue of legal protection for teachers in the performance of their professional duties. This article aims to analyze the legal safeguards available to teachers, particularly in situations involving conflicts with students or their families. The urgency of this research lies in the effort to identify legal loopholes that often place teachers in vulnerable positions, subject to criminalization while carrying out their responsibilities. This study uses a qualitative approach with a library research method, by examining and analyzing relevant literature sources such as books, academic journals, articles, research reports, and other scholarly documents. The findings indicate that there are several legal instruments that regulate the rights and protections of educators. However, implementation is often hindered by a lack of awareness regarding teachers’ rights, as well as an imbalance in resolving conflicts through fair legal mechanisms. The conclusion of this study emphasizes the need for clearer and more practical policies to protect teachers, especially in potentially conflict-prone situations. Such policies are essential to ensure that the teaching profession is respected and protected in accordance with its vital role in upholding the supremacy of law in the education sector.